“But cutting off the Scalps of the Ten Wretches”: Reading Hannah Dustan’s Captivity Narrative through the Body - Veronika Hofstätter (Current Objectives of Postgraduate American Studies)
This paper examines Cotton Mather’s account of Hannah Dustan’s captivity and its representation of white and Native American bodies in the context of an early colonial, Puritan framework. The analysis of the account shows how bodies are used to translate and question concepts of Otherness in early New England. The performance of bodies in the narrative serves as a representational device to utilize agents of ambivalence and deviation from a conventional captivity formula.